An Overview on the Knowledge of Grammar for Paragraph Writing: Exploring the Challenges of Writing in a Second Language (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Writing is a complex cognitive, met cognitive and motor skill activity involving attention at multiple levels thematic, paragraph, sentence, grammatical and lexical. Moreover, writing in second language is a more constrained, more difficult, and less effective. Writers in second language pay little attention to planning, organizing, and generating ideas. Many Indian students, who learn English as a second language, and especially those who experience difficulties with writing, do not exhibit these skills. In other words, they lack self-regulation and composition strategies, skills, and beliefs. Self-regulation of the writing process is critical the writer must be goal-oriented, resourceful, and reflective. Even highly skilled professional writers speak to the demanding and complex mix of composition and self-regulatory abilities involved in writing. Skilled authors also engage in purposeful and active self-direction of these processes and strategies.